A bride for noah ebook - Copeland, Lori (Seattle Brides, 2013)
Lori Copeland and Virginia Smith, beloved authors of the Amish of Apple Grove series, team up again in an exciting new series for devoted fans and new readers. It's 1851, and Evie Lawrence is penniless and heartbroken after a failed romance. When a kind elderly man announces his plan to move west and make his fortune, Evie jumps at the chance to go with him and start a new life. She says goodbye to the only home she's ever known and sets out for the Northwest. There she meets Noah Hughes, a handsome young man who has gambled everything he owns on the chance to make a fresh start. Living the rugged life of a lumberjack, he too is determined to one day make his fortune. The last thing he's looking for is a bride...so why can't he get Evie out of his mind? In this first book of the Seattle Brides series, two people learn what it means to move beyond their expectations and embrace the very best God has for them.